Structural Morphology of Rabbit Patella and Suprapatella Cartilage by Microscopic MRI and Polarized Light Microscopy. (December 2021) - Mantebea, Hannah; Batool, Syeda; Hammami, Mouhamad; Xia, Yang
Objective: In order to appreciate the roles articular cartilage of sesamoid bones and sesamoid fibrocartilage play in anatomy and pathology, the articular cartilage of the patella ( n = 4) and suprapatella ( n = 4) (a sesamoid fibrocartilage) of 12 to 14 weeks old New Zealand rabbits were studied qualitatively and quantitatively. Design/Method: The intact knee joints and block specimens from the joints were imaged using microscopic magnetic resonance imaging (µMRI) at a 97.6-µm pixel resolution for the former and 19.5-µm resolution for the latter. Histological sections were made out of the µMRI-imaged specimens, which were imaged using polarized light microscopy (PLM) at 0.25-, 1-, and 4-µm pixel resolutions. Results: The patella cartilage varied in thickness across the medial to lateral ends of the sesamoid bone with the central medial aspect slightly thicker than the lateral aspect. The suprapatella fibrocartilage decreased proximally away from the knee joint. Quantitative results of patellar cartilage showed strong dependence of fiber orientation with the tissue depth. Three histological zones can be clearly observed, which are similar to articular cartilage from other large animals. The sesamoid fibrocartilage has one thin surface layer (10 µm thick) of parallel-arranged structured fibers followed immediately by the majority of random fibers in bulk tissue. T2 relaxation time anisotropy was observed in the patellar cartilage but not in the bulk fibrocartilage. Conclusion: Given the different functions of these 2 different types of cartilages in joint motion, these quantitative results will be beneficial to future studies of joint diseases using rabbits as the animal model.